APPLICATION OF CHEMICAL CASTRATION LAW FOR PEDOPHILES AS AN EFFORT TO PROVIDE A DETERRENT EFFECTS - Sederhana Ndruru; Steward Chulifier; Irfan Samuel Sirait; Dewi Ervina Suryani (STIH Putri Maharaja, 2022)
Sexual violence is an immoral crime, especially if the act is committed against a child, the act is considered a violation of human rights. Including efforts to overcome the increase in cases of sexual violence against children, the government ratifies PP Nomor. 70 with the aim of regulating procedures for carrying out chemical castration, installing electronic devices as detectors, providing guidance, to how to anNomorunce the personal data of perpetrators of sexual violence against children. The goal is to deter pedophiles from their actions. In its implementation, chemical castration is an act against human rights, giving the punishment of castration including acts that are heiNomorus and Nomort in accordance with human rights, including contrary to our country's commitment to protect human rights. This work is a Nomorrmative juridical legal research type with a qualitative approach. The main sources in this work are Nomor. 70 of 2020 and several other literatures as support. The technique of data collection and analysis is library research. The result of this work is the imposition of sanctions on the perpetrators of chemical equilibrium according to the legal basis. Although it is felt that this law is still experiencing polemics due to the issuance of this new law, the limited age of the perpetrators, and group commentators who still do Nomort support this law.